(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
The onset of the infectious disease Covid19 originating in Wuhan, China, took over the world in December 2019 and was declared a pandemic in January 2020. Empirical evidence resulting from relevant research illustrated that the effects of the pandemic itself but also of the strict measures to contain the spread of the virus on the mental health and well-being of affected populations were just as unanticipated as the pandemic itself. Data led to the identification of six idioms of distress: (1) Demoralization and pessimism towards the future, (2) anguish and stress, (3) self-depreciation, (4) social withdrawal and isolation, (5) somatization, (6) withdrawal into oneself. Our research explores the psychological impact of the Covid19 pandemic on college students and their quality of life. The study took place in Cyprus with 356 young participants, whereas 256 were female (72%) and 100 were male (28%). They all completed the General Health Questionnaire-28 and the Life Satisfaction Inventory (LSI). The present study’s findings revealed that six factors, including residence without family, the deterioration of the financial situation of the family, the loss of employment, the deterioration of social relationships, young age, and gender, have significantly affected in a negative way the mental health and quality of life of young people. Research findings revealed that the strict lockdown and physical/social isolation measures had a significant adverse effect on our sample, whereas participants showed increased symptoms of anxiety and insomnia, social dysfunction, and somatization. Young adults who lost their jobs during the pandemic or had a significant decrease in their family income, and students who stayed away from their families, experienced a negative impact on their quality of life and had to cope with more mental health problems.